Exercise and Conjugated Linoleic Acid Supplementation Induce Changes in the Composition of Liver Fatty Acids - Mika, Adriana; Czumaj, Aleksandra; Stepnowski, Piotr; Macaluso, Filippo; Spinoso, Giulio; Barone, Rosario; Di Felice, Valentina; Sledzinski, Tomasz (Frontiers in Physiology, 2019)
Exercise and supplementation with conjugated linoleic acid (CLA) are used to reduce body weight and to improve health. Applied together, they may exert a synergistic effect. However, the effects of exercise and CLA supplementation on liver metabolism are poorly understood. The aim of this study was to examine the influence of exercise and CLA supplementation on fatty acids (FA) composition in mouse liver. We analysed 44 of known FAs of this organ by gas chromatography-mass spectrometry. Our results demonstrated that exercise contributed to a decrease in odd-chain FA and an increase in n-6 polyunsaturated FA contents. In turn, CLA stimulated an increase in branched-chain FAs and n-3 polyunsaturated FAs. Exercise combined with CLA supplementation caused a substantial increase in branched-chain FA content and a slight increase in n-6 polyunsaturated FAs. The elevated liver content of branched-chain FAs after the exercise combined with CLA supplementation, as well as the increase in n-3 polyunsaturated FAs after CLA may be favorable since both these FA groups were previously shown to produce health benefits. However, the expression pattern of enzymes involved in fatty acid synthesis did not match the changes in FA composition. Thus, the mechanism of exercise- and CLA-induced changes in liver FA profile is yet to be established. Also, the consequences of CLA- and/or exercise-induced changes in the composition of liver FAs need to be elucidated.